2009
DOI: 10.1093/alcalc/agn123
|View full text |Cite
|
Sign up to set email alerts
|

A Promoter Polymorphism in the ALDH2 Gene Affects Its Basal and Acetaldehyde/Ethanol-Induced Gene Expression in Human Peripheral Blood Leukocytes and HepG2 Cells

Abstract: In vivo and in vitro experiments showed that the -360G allele has lower basal transcriptional activity than the -360A allele, whereas acetaldehyde/ethanol-induced gene expression, in general, seems to be more enhanced in individuals homozygous for the -360G allele than in those with the -360A allele. Thus, the promoter polymorphism may be involved in individual differences in acetaldehyde elimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Furthermore, ALDH2 protein expression was lower in patients with the G-allele of rs886205, compared to patients without it on day 1 of withdrawal. As known from previous studies, Gallele-directed impairment of basal ALDH2 gene transcription was shown to be tightly linked to the presence of the respective promoter region upstream of the polymorphic site, as promoter constructs lacking G-allele and the upstream region did not cause decreased promoter activity [10] . With the data presented here, we provide novel information concerning a putative molecular mechanism for the modulation of ALDH2 protein expression involving epigenetic mechanisms contributing to reported health risks due to genetic disposition by rs886205 and combined heavy alcohol consumption [8,9] .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Furthermore, ALDH2 protein expression was lower in patients with the G-allele of rs886205, compared to patients without it on day 1 of withdrawal. As known from previous studies, Gallele-directed impairment of basal ALDH2 gene transcription was shown to be tightly linked to the presence of the respective promoter region upstream of the polymorphic site, as promoter constructs lacking G-allele and the upstream region did not cause decreased promoter activity [10] . With the data presented here, we provide novel information concerning a putative molecular mechanism for the modulation of ALDH2 protein expression involving epigenetic mechanisms contributing to reported health risks due to genetic disposition by rs886205 and combined heavy alcohol consumption [8,9] .…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, the Gallele is known to decrease basal levels of ALDH2 promoter activity and gene transcription both in vitro and in vivo. Interestingly, a specific promoter region upstream the ATG codon of the ALDH2 gene exerts a negative regulatory function on basal ALDH2 promoter activity and mRNA levels in the co-presence of the G-allele of rs886205, while no decrease of basal ALDH2 gene transcription can be assessed in the presence of the A-allele [10] .…”
Section: Introductionmentioning
confidence: 99%
“…As a response to enhance ethanol catabolism, the upregulation of ALDH2 expression has often been observed in several cases of ethanol exposure. For instance, ALDH2 mRNA of peripheral blood leukocytes increases following alcohol ingestion (0.4 g/kg body weight) in healthy young subjects (Kimura et al 2009). In postmortem brain of alcohol-related disorders, elevated expression levels of ALDH2 were observed in the prefrontal cortex (Zhang et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies show that regulation of ALDH2 activity can affect cellular response to oxidative stress [8,9]. ALDH2 activity can be affected by gene regulation [10] or post-translational modifications [11][12][13]. For example, ALDH2 can be directly deacetylated by SIRT3 leading to enzymatic inactivation of ALDH2 [13].…”
Section: Introductionmentioning
confidence: 99%